The Impact of Leadership Styles on Employee Well-Being: A Social Science Perspective - Srigouri Kosuri; Nagesh Mantravadi; Binoy Mathew; Mohan Cherian; Allah Bakash (Metallurgical and Materials Engineering, 2025)
Leadership styles serve as fundamental instruments for forming the way employees and work environments interact as well as staff well-being. The investigation in this paper focuses on how transformational leadership styles and transactional leadership styles and autocratic leadership styles along with laissez-faire leadership styles influence employee psychological levels and emotional well-being and professional development. The research implements both literature review and empirical examinations to discover the main factors behind work environments that become either favorable or unfavorable. Studies show transformational leadership creates positive work relationships between leaders and workers because it enhances their engagement and satisfaction but autocratic leadership typically generates stress and burnout conditions. Research findings present organizations with essential information about establishing supportive workplaces that promote productivity.